From guidelines to evidence-based practice – A German perspective on mesalazine as first-line therapy for mild-to-moderate ulcerative colitis - Schnoy, Elisabeth; Dignass, Axel; Gaskins, Matthew; Kucharzik, Torsten (Zeitschrift für Gastroenterologie, 2025)
Mesalazine is the first-line treatment for mild-to-moderate ulcerative colitis (UC) of any extent, as recommended by all major international and national guidelines. Approximately 85% of UC cases are classified as mild-to-moderate, making mesalazine a cornerstone therapy for the majority of patients. It rapidly induces clinical response and clinical remission, sustains steroid-free clinical, endoscopic, and histologic remission over the long term, and has a safety profile comparable to placebo. This paper reviews the recommendations for mesalazine use in the German UC guideline and provides practical advice (including do’s and don’ts) for their implementation in daily clinical practice. Examples include explaining the expected timeline and nature of the clinical response to mesalazine treatment; outlining the practical implications of the dose-dependency of the drug’s therapeutic effect; and emphasizing the importance of rectal mesalazine as the first-line treatment for proctitis. Additionally, we conducted a systematic literature search to evaluate whether mesalazine should be continued after escalation to biologics or small molecules. While no clear evidence of short-term clinical benefit was found, there was also no evidence of harm. In light of the potential long-term chemoprotective effect of mesalazine, continuation may be considered on a case-by-case basis. Lastly, we provide an overview of the various mesalazine formulations available in Germany, detailing how they are not interchangeable due to differences in drug-release profiles, excipients, and dosing strengths. Understanding these differences may help clinicians personalize treatment, improving adherence and clinical outcomes.
Keywords: 5-aminosalicylic acid; evidence-based practice; guidelines; mesalamine; mesalazine; mild-to-moderate UC; ulcerative colitis